Specifics of simultaneous translation of abbreviations (Ta'limning zamonaviy transformatsiyasi, 2024)
This article will delve into the specifics of simultaneous translation of abbreviations, the challenge of abbreviations in simultaneous translation, strategies for accurate translation of abbreviations, enhancing communication through skillful abbreviation translation, exploring the challenges linguists face and the strategies they employ to ensure seamless communication across languages.